Peningkatan Mutu Pendidikan Melalui Manajemen Kurikulum yang Efektif Bagi Sekolah Menengah Atas di Kota Samarinda - Harliansyah Harliansyah (Literasi Nusantara Publisher, 2022)
This study describes the management of the educational curriculum in improving the quality of education in senior high schools in Samarinda City. This research was conducted using a qualitative approach and data collection techniques through observation, documentation, and interviews. Data analysis was carried out in the following stages: compiling, linking, reducing, presenting, and concluding. The results of the study show that: 1) School curriculum planning always emphasizes the importance of the school's vision and mission aspects, the changes that occur in the education process, adjusted to the national education curriculum program and the local curriculum, as well as the conditions and needs of the school. 2) Organizing the curriculum, giving assignments and authority by the school principal to the curriculum coordinator, namely the vice principal and senior teacher to oversee the learning process. 3) The educational curriculum is implemented with an academic design and calendar and involves all school members. 4) Curriculum supervision is carried out by examining learning tools, such as teaching materials, and planning the implementation of learning media.